Detection of Lactic Acid Bacteria (LAB) In Soaking Water of Arabica Coffee Cherries on Mount Sindoro - Windy, Windy; Dewi, Lusiawati (Riviera Publishing, 2023)
Coffee is one of the major commodities in Indonesia's agricultural sector, where Indonesia is the fourth largest coffee producer in the world. Arabica coffee is the only type of coffee produced on Mount Sindoro. The used water is wasted in the sewers when washing and sorting coffee. Even though the skin covering the cherry flesh is likely to contain natural microorganism life since the coffee cherries grow during ripening on the tree. Therefore, this study aims to determine whether there is the presence or absence of Lactic Acid Bacteria (LAB) groups in the water used to soak the Arabica coffee cherries. The research method was carried out with 200 ml of water samples soaked in Arabica coffee cherries for 4 hours, isolating microorganisms from the 10-1 to 10-3 dilution series of soaking water using the spread plate method and reinoculation to obtain pure LAB cultures, then detected macroscopically through observation of colony morphology and microscopically detected, including physiological and biochemical reaction tests. Data analysis was conducted in a fully descriptive-qualitative manner concerning Bergey's Manual of Determinative Bacteriology and other books supporting the detection of the BAL groups obtained. The study results obtained three isolates, but only one isolate was detected as LAB. The isolate belongs to the Streptococcaceae family's LAB group- the Lactococcus genus.